"Selling Girls in Kuwait": Domestic Labour Migration and Trafficking Discourse in Nepal - O’Neill, Tom (Anthropologica, 2022)
The pace of economic globalization is accelerating, ironically, at a time when the movement of human capital is becoming more restricted. As the potential for legal migration is denied by states to would-be migrants, illegal networks form that place them at greater risk of exploitation. This paper examines a scheme by which Nepalese girls were "trafficked" to Kuwait to work as domestic workers, and how this was constructed as their immoral objectification by the Nepalese media and an anti-child exploitation NGO. I argue that "discourses of national honour," which hold girl children as the legitimate objects of state protection places opprobrium on those who facilitate illegal migration and ignores the decision-making of the migrants and their families. A meaningful discourse on the nature of a "new world order" for migrant workers must balance risk and autonomy for all migrants, regardless of gender or age.